Program Police Goes To School Dalam Menekan Angka Laka Lantas Oleh Unit Dikyasa Polres Tasikmalaya - andra, roby (Advances in Police Science Research Journal, 2020)
In 2016 vehicles population in Indonesia reached 124,348,224 units. This shows the high number of riders in Indonesia. This situation poses problems such as traffic accidents. Traffic accidents can occur as a result of an unorderly drive caused by a lack of understanding of the orderly traffic. This research aims to describe and analyse the process of implementing the Police Program Goes to School as well as to identify the supporting and blocking factors of the program's implementation to suppress the traffic accident figures of Tasikmalaya regional police. This research uses qualitative methods with the analysis descriptive technique. Data is validated and analyzed by communication, management and SWOT theory. Police Program Goes to School by Polres especially traffic Dikyasa Unit has been carrying out the program Dikmas then to the fullest. However, the number of accidents that occurred in Tasikmalaya district especially in the category of high school students is relatively high. The unit of traffic and the school’s stakeholder play a pivotal role in the conduct of the education of orderly traffic so it needs another program that is more effective.